2010
DOI: 10.1162/qjec.2010.125.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Free Distribution or Cost-Sharing? Evidence from a Randomized Malaria Prevention Experiment*

Abstract: It is often argued that cost-sharing-charging a subsidized, positive price-for a health product is necessary to avoid wasting resources on those who will not use or do not need the product. We explore this argument through a field experiment in Kenya, in which we randomized the price at which prenatal clinics could sell long lasting anti-malarial insecticide-treated nets (ITNs) to pregnant women. We find no evidence that costsharing reduces wastage on those that will not use the product: women who received fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
425
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(470 citation statements)
references
References 52 publications
(36 reference statements)
23
425
6
1
Order By: Relevance
“…In some cases, rigorous, randomized control trials can test specifi c hypotheses about aid initiatives and policies ( 16). For example, recent experiments in Kenya found that providing free malaria bednets could save more lives than cost-sharing programs, thus overturning previously held assumptions about how to fi nance such basic interventions ( 17).…”
Section: Ensuring Results On the Groundmentioning
confidence: 99%
“…In some cases, rigorous, randomized control trials can test specifi c hypotheses about aid initiatives and policies ( 16). For example, recent experiments in Kenya found that providing free malaria bednets could save more lives than cost-sharing programs, thus overturning previously held assumptions about how to fi nance such basic interventions ( 17).…”
Section: Ensuring Results On the Groundmentioning
confidence: 99%
“…One study in Kenya testing the effect of prices on bednet take-up and use among pregnant women found no evidence that cost-sharing increases the likelihood that bednets end up in the hands of women who need them the most. Those who paid higher prices were no sicker than those in the comparison group, as measured by anemia status, an important indicator of malaria [5]. * The study also found that those who take the bednets for free are just as likely to use them as those who pay more (see the graph below).…”
Section: Supporting Evidencementioning
confidence: 87%
“…For example, take-up of insecticide-treated bednets among pregnant women at antenatal care clinics in Kenya dropped by 60 percentage points (from 99 percent to 39 percent) when the price increased from zero to US$0.60 [5]-an amount that still represented a 92 percent subsidy of the US$7 market price [6]. The drop-off in purchase rate occurs even among households that could highly benefit from the product.…”
Section: Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…This issue has notably been addressed by Cohen and Dupas (2010) in a randomised experiment on pregnant women in Kenya where it is found that the demand for ITNs is highly price sensitive and cost-sharing is not more cost-effective, in terms of child mortality, than free distribution. However, this is not the focus of our analysis.…”
Section: Introductionmentioning
confidence: 99%